Design of an MIMO dielectric resonator antenna for 4G applications - Nasir, Jamal (Springer New York LLC, 2016)
A two-port MIMO Dielectric Resonator Antenna (DRA) has been proposed and studied. The antenna consists of a single Rectangular DRA (RDRA) element housed in a thin FR4 substrate, that is fed by two microstrip feed lines. Both the feeding lines excite (Formula presented.) mode in the RDRA. The mutual coupling between the ports has been decreased by employing two symmetrical slits in the ground plane. The proposed antenna has been fabricated and a parametric study has been carried out to obtain the optimum parameters. The presented antenna with acceptable MIMO characteristics, covers a measured bandwidth of 80 MHz (2.56–2.64 GHz) for |S11| < −10 dB, which is able to operate on LTE band 38. The measured isolation between the two ports for the desired frequency band is better than 20 dB. The presented antenna has been examined by calculating and measuring the Envelope Correlation Coefficient, Mean Effective Gains and the Diversity Gain. Based on the study that has been carried out, the antenna offers easy fabrication, feeding and good MIMO characteristics. Therefore, the presented antenna can be a suitable candidate for LTE applications.